Bacterial Transcriptional Control Methods and Protocols - Artsimovitch, Irina (Springer, 2015)
Cellular multisubunit RNA polymerases are essential for all extant life, share a common ancestry, and utilize similar mechanisms to regulate their biochemical activities, molecular movements, and recruitment to specific loci that is critical to timely and accurate gene expression. This book is designed to provide a resource of proven techniques and approaches to probe the activities of bacterial, eukaryotic, and archaeal RNA polymerases. The volume is by no means an all-inclusive collection of techniques available to the field; instead, we intended to highlight the breadth and depth of techniques that are likely to continue to shape the transcription community in the future...